Integration of Terahertz Spectroscopy with Microfluidic Platforms for Early Cancer Biomarker Detection - Zainab Ali Abdul Hussein Karim; Karrar Mohammed Fadil; Youssef Mohammed Abbas; Nour Fadhil Fajr; Naba Gasam Anoon (American Journal of Biomedicine and Pharmacy, 2025)
Cancer is becoming one of the biggest health problems over the world. A lot of in-depth research results and clinical diagnosis show that cancer cells have different molecular subtypes. Detection of cancer from molecular level such as DNA or RNA instead of pathology or histology could help doctors to perform early detection and treatment. Trace amounts of cancer biomarkers in serum were found to reflect the existence of tumor cells. Therefore, detection of cancer biomarkers such as enzymes and specific protein is believed to be one of the effective methods in early detection of cancer.